2016
DOI: 10.1016/j.electacta.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Soluble tetratriphenylamine Zn phthalocyanine as Hole Transporting Material for Perovskite Solar Cells

Abstract: For the manuscript EO16-1873: "Soluble tetratriphenylamine Zn phthalocyanine as Hole Transporting Material for Perovskite Solar Cells".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 29 publications
(12 reference statements)
1
23
0
Order By: Relevance
“…With considerable attention, CuPc and their derivatives have recently been utilized as a hole‐transporting layer (HTL) in PSCs with long‐term durability . Although soluble copper phthalocyanine has already been studied and published previously, the poor solubility of CuPc restricts its application in solution‐processable PSCs . Copper phthalocyanine‐3,4′,4′′,4′′′‐tetra‐sulfonated acid tetra sodium salt (TS‐CuPc) possesses good solubility in polar solvents, which brings to the potential application in low‐cost PSCs as an HTL.…”
Section: Introductionmentioning
confidence: 99%
“…With considerable attention, CuPc and their derivatives have recently been utilized as a hole‐transporting layer (HTL) in PSCs with long‐term durability . Although soluble copper phthalocyanine has already been studied and published previously, the poor solubility of CuPc restricts its application in solution‐processable PSCs . Copper phthalocyanine‐3,4′,4′′,4′′′‐tetra‐sulfonated acid tetra sodium salt (TS‐CuPc) possesses good solubility in polar solvents, which brings to the potential application in low‐cost PSCs as an HTL.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they increased the PCE to 13.65% by using a mixture of 16 and Al 2 O 3 as the buffer layer. 55 Gao et al synthesized a symmetric zinc Pc 17 bearing four thiophene groups with low bandgap characteristics as a HTM in perovskite solar cells. 56 They observed the time-resolved PL decay at the perovskite/compound 17 interface and revealed that 17 exhibited the quick quenching as same as spiro-OMeTAD.…”
Section: Phthalocyanines As Hole-transport Materials In Perovskite Somentioning
confidence: 99%
“…After that, this group reported the replacement ofthe n‐butyl chain with triphenylamine and Cu(II) metal with Zn(II) in phthalocyanine. With the triphenylamine, improved electron cloud at core moiety, the solubility and uniform film formation all act favorably for this compound to be a potential HTM in PSCs . Triphenylamine‐substituted Zn phthalocyanine‐based solar cells exhibited 5.6 % efficiency without additives and with additives 9.0 % was achieved.…”
Section: Macrocyclic Metal Complex Derivatives As Hole Transporting Mmentioning
confidence: 99%
“…The Al 2 O 3 layer avoids pinholes and shunt paths towards both the electrodes in the device. The Al 2 O 3 layer offers more hole filling layer, improving the overall performance of the device; the efficiency enhanced from 9.0 to 13.65 %, other parameters are listed in Table and .…”
Section: Macrocyclic Metal Complex Derivatives As Hole Transporting Mmentioning
confidence: 99%